Legal Study of The Existence of Genuine Autonomy in Order to Organize Village Autonomy in Indonesia - David Aprizon Putra; M. Anton Alifandi (NEGREI: Academic Journal of Law and Governance, 2021)
The centralized system implemented by the New Order government made the central to regional movements only as the form of exploitative movements. Meanwhile, the movement from the regions to the center has only become an enslaving movement. This fact then became the basis for the formation of genuine autonomy, which seeks to turn imperial cosmopolitanism into micro-politics in the form of regional autonomy. This was followed by the birth of Village autonomy in 2014, which certainly brought fresh air in the governance development order in Indonesia. The effort to restore the essence of genuine autonomy, which is indeed a pure value that has existed and belonged to the archipelago, is one of the gold goals for implementing this village autonomy. This legal research uses a normative-sociological approach based on statutory data, literature studies and history. There are many significant things related to strengthening the existence of Genuine Autonomy/Village Autonomy in Law Number 6 of 2014 concerning Villages. We can see this in terms of: Regarding the definition of village (Article 1 point 1), Setting 10 percent of APBN funds to be allocated to the Village, Regarding to the evolution of village authority (Articles 18 and 19), Regarding the portion of village rights [Article 6 act (1 )], Regulation on Village-Owned Enterprises (Article 87). There are several things we can do in an effort to maintain the existence of genuine autonomy/village autonomy in Law Number 6 of 2014 concerning Villages: 1). Legislative: The need of a strong legal certainty foundation; 2). Executive: The need for Government Apparatus with integrity, professional, neutral, and noble character, Community Participation; 3). Community: Strong and Participatory Civil Society